4-H Club Program Planning Guide—A Guide for Staff and Volunteers - Joy C. Jordan; Dale Pracht; Judy Butterfield (EDIS)
4H GCL20, an 8-page guide by Joy Jordan, Dale Pracht, and Judy Butterfield, will help 4-H club leaders and staff effectively plan a successful and exciting year. Layout and design have been revised. Published by the UF Department of Family, Youth and Community Sciences, November 2007.